Mastectomized women: experiences front to the breast cancer - Claudelí Mistura; Maria de Fátima Alvez Aguiar Carvalho; Viviane Euzébia Pereira Santos (Universidade Federal de Santa Maria, 2011)
This study aimed to identify how mastectomized women face cancer and chemotherapy treatment. It adopted a descriptive with a qualitative approach. Six mastectomized women with breast cancer and under chemotherapy treatment were interviewed at APAMI in the city of Petrolina - PE. The data collecting was made from recorded semi-structured interviews, based on a pre-established script. The data obtained were submitted to the Content Analysis Technique proposed by Bardin, split into two categories: from the diagnosis to treating the breast cancer and the strategies to face the chemotherapy treatment and the breast cancer. As result the study highlighted several types of feelings experienced by the group such as: depression, anguish, sadness and anxiety. Among the set in motion devices to cope with the problem are the familial and religious support. The conclusion is that the care addressed to these women must be performed by a multi-professional team, providing them with full assistance, contemplating them in their multiple dimensions